Attenuation of cell adhesion in lymphocytes is regulated by CYTIP, a protein which mediates signal complex sequestration - Boehm, Thomas (Oxford University Press, 2003)
An important theme in molecular cell biology is the regulation of protein recruitment to the plasma membrane. Fundamental biological processes such as proliferation, differentiation or leukocyte functions are initiated and controlled through the reversible binding of signaling proteins to phosphorylated membrane components. This is mediated by specialized interaction modules, such as SH2 and PH domains. Cytohesin-1 is an intracellular guanine nucleotide exchange factor, which regulates leukocyte adhesion. The activity of cytohesin-1 is controlled by phospho inositide-dependent membrane recruitment. An interacting protein was identified, the expression of which is upregulated by cytokines in hematopoietic cells. This molecule, CYTIP, is also recruited to the cell cortex by integrin signaling via its PDZ domain. However, stimulation of Jurkat cells with phorbol ester results in re-localization of CYTIP to the cytoplasm, and membrane detachment of cytohesin-1 strictly requires co-expression of CYTIP. Con sequently, stimulated adhesion of Jurkat cells to intracellular adhesion molecule-1 is repressed by CYTIP. These findings outline a novel mechanism of signal chain abrogation through sequestration of a limiting component by specific protein–protein interactions.